PENGEMBANGAN VARIETAS UNGGUL TANAMAN SERAI WANGI DI DESA SIDORUKUN KABUPATEN LABUHANBATU - Siti Hartati Yusida Saragih, Kamsia Dorliana Sitanggang, Widya Lestari, , Rohani (JURNAL BIMA, 2023)
The Farmer Work Group (KTK) of Pangkatan Village, Sidorukun District, Labuhanbatu Regency on its own initiative has been cultivating citronella (Cymbophogon nardus) since 2019. The obstacles faced by CEC today are limited public information on superior varieties of citronella and the benefits of citronella oil content. The purpose of this community service activity is to increase public knowledge about how to recognize and distinguish superior varieties of citronella plants and their content. This community service method is carried out by counseling in the form of material presentation and discussion about superior varieties and essential oil content in citronella. The material presented included training on the introduction of superior varieties and socialization of essential oil content in citronella. In the training process, the speaker interspersed it with several demonstrations and question and answer discussions. The results of the evaluation of activities showed an increase in public knowledge about several superior varieties of quality citronella oil.